2022
DOI: 10.1891/jpe-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Health Workforce Challenges Impact the Development of Robust Doula Services for Underserved and Marginalized Populations in the United States

Abstract: Evidence of doulas’ positive impacts on maternal health outcomes, particularly among underserved populations, supports expanding access. Health workforce-related barriers challenge the development of robust doula services in the United States. We investigated organizations’ barriers regarding training, recruitment, and employment of doulas. We conducted literature and policy reviews and 16 semi-structured interviews with key informants who contribute to state policymaking and from organizations involved in tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…One record called for the consideration of such requirements by both large and community-based organizations training doulas (Van Eijk, Guenther, Kett, et al, 2022). Another underscored the workforce diversity-related implications of the prohibitive costs of training and certification for community doulas serving populations historically underserved by the maternal health care system (Van Eijk, Guenther, Jopson, et al, 2022). Those authors, who collected semi-structured interview data from key informants representing a variety of perspectives reflecting those who contribute to state policymaking, found that community-based, relative to mainstream, doula training organizations tended to recruit trainees from underserved communities identified as in need of doula services—which are often communities of color (Van Eijk, Guenther, Kett, et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…One record called for the consideration of such requirements by both large and community-based organizations training doulas (Van Eijk, Guenther, Kett, et al, 2022). Another underscored the workforce diversity-related implications of the prohibitive costs of training and certification for community doulas serving populations historically underserved by the maternal health care system (Van Eijk, Guenther, Jopson, et al, 2022). Those authors, who collected semi-structured interview data from key informants representing a variety of perspectives reflecting those who contribute to state policymaking, found that community-based, relative to mainstream, doula training organizations tended to recruit trainees from underserved communities identified as in need of doula services—which are often communities of color (Van Eijk, Guenther, Kett, et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…For recruitment, we built upon our previous national study in which we interviewed members of organizations that train, recruit, and employ birth doulas. 23,28 Drawing on these relationships and network connections, as well as directories provided by national associations which support and fund doulas of color and additional keyword searches, we identified over 75 individual birth doulas and doula organizations working with underserved and historically excluded populations across the country. We created a matrix with their names, email addresses, occupational settings (including self-employment), and location.…”
Section: Interviewee Recruitmentmentioning
confidence: 99%